2008
DOI: 10.1002/cjce.5450840503
|View full text |Cite
|
Sign up to set email alerts
|

Spouting Enhancement by Addition of Small Quantities of Liquid to Gas-Spouted Beds

Abstract: L'ajout d'eau liquide à des lits de particules de polystyrène de plus de 3 mm de diamètre améliore le jaillissement en causant une diminution de la vitesse de jaillissement minimale. Alors que le degré d'amélioration est du point de vue quantitatif comparable à ce que nous avons indiqué antérieurement pour des lits fl uidisés à larges particules hydrophobes légères, le mécanisme est différent. L'amélioration du jaillissement se produit parce que le liquide s'agglomère à l'interface jet-espace annulaire, forman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Continued liquid injection results in saturation of the liquid inside the bed with enhanced particle displacement only in the spout with particle lump formation, which can clearly be observed close to the bed wall in the annulus Figure l. This may be due to the reduced minimum fluidization and spouting velocity . Also, for the nonporous particles, the added liquid occupies a certain space between the particles, which causes an increase in the interstitial gas velocity.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Continued liquid injection results in saturation of the liquid inside the bed with enhanced particle displacement only in the spout with particle lump formation, which can clearly be observed close to the bed wall in the annulus Figure l. This may be due to the reduced minimum fluidization and spouting velocity . Also, for the nonporous particles, the added liquid occupies a certain space between the particles, which causes an increase in the interstitial gas velocity.…”
Section: Resultsmentioning
confidence: 95%
“…4 and 5. Further, Nagahashi et al studied the effect of water addition in a half cylindrical spouted bed with and without draft tube for polystyrene particles ( d p = 6 mm) and compared the results with previous experiments performed on fluidized beds. Their results revealed that injection of liquid in a spouted bed leads to a lower minimum spouting velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The spouting enhancement of polystyrene beads based on minimum spouting velocity lubricating with water addition was attributed (Nagahashi et al, 2006) to a lubricating effect of the liquid on the bed particle motion. Also, the authors refer to liquid congregation at spout-annulus interface, forming an effective nearly impermeable draft tube and increasing air velocity in the spout.…”
Section: Wet Bed Fountain Height and Pressure Dropmentioning
confidence: 97%
“…This regime was observed for several conditions and was called incoherent spouting. When liquid is fed onto the inert bodies, it causes a lubricating effect and according to Nagahashi et al (2006) liquid congregation at spout-annulus interface is observed, forming an effective nearly impermeable draft tube. This may cause the channelling of air in spout, eliminating the formation of bubbles.…”
Section: Analysis Of Pressure Fluctuationmentioning
confidence: 98%
See 1 more Smart Citation